Disclosure of Beneficial Ownership after the Panama Papers - Fenwick, Mark; Vermeulen, Erik P.M. (International Finance Corporation, Washington, DC, 2016)
Publication of the so-called “Panama Papers” focused public interest on how certain politicians, celebrities, and other elites may have used elaborate corporate structures and offshore tax havens to conceal their beneficial ownership of companies and obscure their personal assets. Rather than taking the Panama Papers as an indication of the need for more and stricter disclosure and reporting rules, this paper advocates an alternative approach. We need to start by acknowledging that many companies are currently experiencing "disclosure and reporting fatigue", in which the constant demand for “more” and “better” transparency and reporting is having the unintended effect of promoting indifference or evasiveness. The practice of disclosure and reporting is widely perceived as an obligation to be fulfilled and not as an opportunity to add value to a firm. This is confirmed by the findings of an empirical study conducted by the authors of this paper that examines how disclosure rules operate in practice across various jurisdictions. The key takeaway of the study is that—even in jurisdictions that have a robust disclosure regime—the majority of firms engage in “grudging” or “boilerplate” compliance, in which ownership and control structures are not adequately revealed in an accessible way and, perhaps more importantly, the impact of these ownership and control structures on the governance of a company is obscured. In this paper the authors advocate an approach based on the current communication strategy of a minority of firms in their sample—firms that engage in what the authors characterize as “open communication.” These firms present information on control structures—and their effect on governance—in a direct, accessible, and highly personalized manner. Such firms seem to recognize the commercial and other strategic benefits to be gained from open communication. The paper explores the implications of such an approach for both business and regulators.